EFFECTIVENESS OF DISTANCE LEARNING OF PHYSICS OF TECHNICAL SPECIALTIES STUDENTS UNDER QUARANTINE CONDITIONS - Ishchenko, Ruslan; Gorbunovich, Iryna (Physical and Mathematical Education, 2021)
Formulation of problem. Nowadays, distance learning is especially relevant when the educational process is carried out through the use of modern information and communication technologies. Physics is known to belong to the cycle of compulsory disciplines of natural sciences and mathematics, which is studied by students of technical specialties. At the same time, physics is traditionally one of the most difficult disciplines for most students. Accordingly, the study of the effectiveness of distance learning of physics by students of technical specialties in quarantine conditions is relevant. Materials and methods. The results of students’ success of technical specialties of the National Transport University in physics based on the results of full-time and distance learning were processed. The number of students was 242 people. To achieve the purpose of the work, the following methods are used: analysis and systematization – during the review of scientific publications on the chosen subject of research; analysis, synthesis, comparison, systematization, generalization – during the processing and discussion of the student achievements in physics based on the results of full-time and distance learning. Results. In the presented work it is revealed that the distribution of final grades in physics based on the results of full-time and distance learning is quite different. In particular, according to the results of distance learning of physics, we can distinguish the two largest subgroups of students who received maximum (A) and minimum (E) final grades, correspondently. This trend is observed in each academic group of students. The level of quality of education, which is the percentage of students who received final grades A, B and C in physics, during distance learning is 50.8 %, that is 5.8 % higher than during full-time education. Conclusions. Thus, the distance learning of physics of technical specialties students during quarantine has replaced the full-time education with sufficient effectiveness. However, distance learning of physics in the modern format has proved to be less appropriate for students with a low level of self-organization. These students are psychologically unprepared for distance learning and, accordingly, receive minimal final grades in physics. In future, according to the authors, a mixed form of education of physics should be more effective.